(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the clinical efficacy and compare the attitudes of patients towards the benefits and cost of routine scaling and polishing and to compare the experience of using manual versus ultrasonic instruments to scale teeth. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Out Patient Department (OPD) in dental block at Darul Sehet Hospital, Karachi from July 2019 to December 2019. Materials and Methods: A cross sectional study conducted involving 40 adult volunteers attending Out Patient Department (OPD) in dental block at Darul Sehet Hospital. Participants were healthy adults with no significant periodontal diseases randomly allocated to two groups to receive scaling and polishing.50 patients participated in this study. Patients were randomly allocated to either group. Patients' attitudes towards, and experience of, the scaling and polishing were elicited by means of self-administered questionnaires. Results: The majority of patients (99%) believed a scaling and polishing was beneficial. Patients considered ultrasonic treatment to be appropriate on significantly more occasions than they did for manual scaling and polishing (P < 0.001). Patient discomfort: with ultrasonic scaling 69.2% felt 'a little uncomfortable' or worse compared with 60% of those undergoing manual treatment (P = 0.072). Conclusion: Routine scaling and polishing is considered beneficial by patients. The majority of patients, regardless of treatment method, experience some degree of discomfort when undergoing a scaling and polishing procedure.